The productivity shock in business services - Alexander S. Kritikos; Alexander Schiersch; Caroline Stiel (Small Business Economics, 2022)
In Germany, the productivity of professional services, a sector dominated by SME, declined by 40 percent between 1995 and 2014. Similar developments can be observed in several other European economies. Using a German dataset with 700,000 firm-level observations, we analyze this largely undiscovered phenomenon in professional services, the fourth largest sector of the business economy in the EU-15, which provides important inputs to the economy and has experienced substantial growth in both output and employment since the turn of the millennium. We find that changes in the value chain explain about half of the decline and that increases in part-time employment account for another small part. Contrary to expectations, the entry of micro and small firms is not responsible for the decline, despite their lower productivity levels. Further, we cannot confirm the conjecture that weakening competition has led to an increase in the number of unproductive firms remaining in the markets and that this has led to a lower average productivity.
Keywords: D24; L11; L26; L84; O47; 330; Business services; Labor productivity; Productivity slowdown